Continuous release of SO4˙− over g-C3N4/ZnO/Fe(iii) systems mediated by persulfates: the Fe(iii)/Fe(ii) cycling and degradation pathway. Issue 7 (4th March 2020) - Liu, Shaomin; Zhang, Jianshu; Chen, Meiling; Wang, Xiaoxiao
Abstract : A process to obtain Fe(ii ) by photogenerating electrons for the activation of persulfates and durable release of sulfate free radicals was proposed. Abstract : A novel method of the continuous activation of persulfates will improve the possibility of persulfates entering the actual wastewater. The main purpose of this study was to use a g-C3 N4 /ZnO catalyst to reduce Fe(iii ) to activate persulfates, effectively degrade rhodamine B (RhB) under visible light irradiation, and analyze the degradation process and mechanism of RhB. First, the g-C3 N4 /ZnO catalyst was prepared by a simple calcination method. Second, the photocatalyst was used to generate photoelectrons that reduced Fe(iii ) to Fe(ii ) and then, Fe(ii ) was used to activate the persulfates and release the sulfate radicals. The as-prepared samples were characterized by XPS, EDS, XRD and TEM. The optimal conditions (light intensity, catalyst dosage and anions) were investigated for the degradation of RhB, and the experiments of different pollutants were compared under the same conditions. Finally, RhB was oxidized by hydroxyl radicals and sulfate radicals to make it completely mineralized. During the whole degradation process, the holes and photoelectrons generated by the photocatalyst were involved in the degradation of pollutants in the form of hydroxyl radicals and sulfate radicals, respectively. This not only improves the efficiency of electron and hole separation, but also greatly improves the utilization of light energy, due to which the use of light energy is not limited to a single hole or photoelectron. The theory and method of using photogenerated electrons to obtain Fe(ii ) to activate persulfates and continuously release sulfate free radicals were proposed, which provided an idea for the application of photocatalytic Fenton-like reactions in practical engineering in the future.